Standards of Excellence from a Leader of Excellence: Honoring Our Professional Heritage and Remembering Daniel L. Stufflebeam - Michael Q. Patton (Journal of MultiDisciplinary Evaluation)
Pays tribute to Stufflebeam's leadership in developing evaluation standards and their impact on professionalizing the evaluation field.